STRATEGI PENGEMBANGAN INDUSTRI OLAHAN MAKANAN RUMPUT LAUT (Studi Kasus: Industri Rumah Tangga Narasa di Palu Utara) - Musthofa, M. Jauhar (JSTT, 2014)
The objective of this research was to identify the internal factors (the strength and weakness), the external one (opportunity and threat) and to state the alternative of development strategy for Narasa Home Industry. It was carried out in Narasa home industry of North Palu. The sampling was done purposively. Environment analysis, SWOT, and QSPM is used to analyze the development strategy decision. The analysis referred to the EFE matrix and IFE producing the biggest power, namely the good quality of material, the biggest weakness is uninteresting product package; the biggest opportunity is the support of Palu Government while the biggest threat is the increasing of raw materials and additional material prices. The result of industrial position determination and the SWOT analysis were S-O strategy to increase the quality, defend the products price, promote and penetrate market with target of middle class of society. QSPM analysis resulting the most interesting strategy for the development of this industry is increasing the quality and defending the price.